MuSK-Myasthenia Gravis Unmasked by Hydroxychloroquine - Shalini Bhaskar; Mohammed Fauzi Bin Abdul Rani (Case Reports in Medicine)
Introduction. Muscle-specific tyrosine kinase (MuSK) antibody positive myasthenia gravis (MuSK-MG) is a rare clinical disorder, and diagnosing it can be challenging. Most of the patients present with predominant facial, oculo-bulbar, and neck muscle weakness along with respiratory muscle involvement. Such a presentation can be mistaken for bulbar onset motor neuron disease or as one of the rare oculopharyngeal myopathies. Case Report. We present a young female patient, who reported to us with neck muscle weakness, ocular and bulbar muscle paralysis, and breathing difficulty. She had been healthy till she was prescribed hydroxychloroquine (HCQ) tablets (400 mg per day) for a malar rash. By the end of the second week after commencing the HCQ therapy, she developed the muscle weakness. Her symptoms began to regress after stopping HCQ and starting steroids, pyridostigmine, and, subsequently, azathioprine. She was negative for anticholinesterase receptor antibodies (AChR-Ab) but was positive for MuSK antibodies (MuSK-Ab). Conclusion. This report proves that MuSK-MG can also be unmasked by HCQ administration. Awareness of drug-induced/-unmasked MG is important, as failure to do so may result in a severe morbidity and a fatal outcome. The offending drug has to be promptly discontinued, and appropriate treatment should be instituted.